Antimicrobial Susceptibility Pattern of Bacterial Isolates In Neonatal Sepsis at the Special Care Neonatal Unit Of Chittagong Medical College Hospital - Akter, Humayra; Hasan, Syeda Humaida; Khan, Md Masudur Rahman; Shaheen, Mohammed; Chowdhury, Muhammad Jabed Bin Amin; Hossain, Mir Mosharof (Journal of Chittagong Medical College Teachers' Association, 2025)
Background: Neonatal sepsis is one of the leading causes of neonatal mortality in Bangladesh. To effectively treat and prevent neonatal sepsis, continuous monitoring of microbial etiology and antimicrobial resistance profiles is essential in neonatal care units. This study aimed to identify the pathogens responsible for neonatal sepsis and understand their current antimicrobial resistance pattern. Materials and methods: This retrospective study was conducted in the Neonatal Intensive Care Unit (NICU) of Chittagong Medical College Hospital, Chattogram from July, 2023 and March 2024. All neonates with a positive blood culture were identified. Patient demographics, clinical details and laboratory data including bacteriological profiles and antimicrobial susceptibilities were recorded and analyzed. Results: The majority of the 108 culture-positive neonates were preterm (73.1%) and had low birth weight (78.7%). Most of them had late onset sepsis (66.7%). Most bacterial isolates were gram-negative, predominantly the Klebsiella (46.3%) which showed high resistance to commonly used antibiotics such as, Gentamicin (85.2%) Amikacin (78%) Cefepime (97.2%) and Meropenem (69.2%) and good susceptibility to Colistin (86.8%) and Tigecycline (95.1%). Among gram-positive isolates, Coagulase Negative Staphylococci (CONS) (13.8%) predominated. CONS showed high resistance to Meropenem (80%), Tazobactam-piperacillin (70%) and Cefepime (75%) but good susceptibility to Tigecycline, Vancomycin and Linezolid (100%). Nearly, two-third organisms were MDR (69.1%) and one-third were XDR (37.1%). Deaths were more common among preterm, late onset sepsis, nosocomial sepsis and sepsis with MDR organisms. Conclusions: Klebsiella and CONS were the most common causes of neonatal sepsis in our study with an alarming prevalence of MDR strains. Implementation of effective preventive strategies to combat the emergence of antibiotic resistance is urgently needed. JCMCTA 2024 ; 35 (2) : 117-123